Myxedema Crisis Presenting with Seizures: A Rare Life-Threatening Presentation—A Case Report and Review of the Literature - Sonali Sihindi Chapa Gunatilake; Uditha Bulugahapitiya (Case Reports in Endocrinology)
Myxedema crisis is a life-threatening extreme form of hypothyroidism with a high mortality rate if left untreated. Myxedema crisis is commonly seen in older patients, especially in women, and is associated with signs of hypothyroidism, hypothermia, hyponatraemia, hypercarbia, and hypoxemia. Patients might present with different organ specific symptoms. Seizures are a recognized but rare manifestation of myxedema with a very high mortality rate. Prompt diagnosis and appropriate management may improve the prognosis. Many contributory factors may involve development of seizures in a patient with myxedema. Hyponatraemia is one such cause, which is seen in moderate-severe form in the background of myxedema. We report an elderly male who presented with generalized tonic clonic seizure preceded by memory impairment and drowsiness. He had moderate hyponatraemia and very high thyroid stimulatory hormone levels in association with low free thyroxin levels. Diagnosis of myxedema crisis was made and patient was successfully treated with sodium correction and thyroid hormone replacement.